HIF-1α alleviates ferroptosis in ulcerative colitis by regulation of GPX4 - Weitao Hu; Yanliang Cai; Daxing Cai; Zongchi Chen; Siying Huang; Su Zhang; Huie Zhuang; Taiyong Fang; Xiaoqing Chen (Cell Death and Disease)
Abstract Ferroptosis is an iron-dependent form of regulated cell death induced by the lethal accumulation of lipid peroxidation, while the precise mechanism of ferroptosis in the pathogenesis of ulcerative colitis (UC) remains to be elucidated. This study aimed to explore the potential effect of hypoxia inducible factor-1α (HIF-1α) on ferroptosis in intestinal epithelial cells (IECs) in UC. The relationship between ferroptosis and HIF-1α was initially investigated using clinical UC colon samples. In vitro and in vivo models of acute intestinal inflammatory response were constructed using lipopolysaccharide (LPS) and dextran sulfate sodium (DSS), respectively. The effect of HIF-1α on ferroptosis in UC was determined by establishing HIF-1α overexpression (HIF1A-OE) or knockdown (shHIF1A) IEC lines, and the mechanism by which HIF-1α mediated the transcription of glutathione peroxidase 4 (GPX4) was explored by combining Co-immunoprecipitation (Co-IP) and Chromatin immunoprecipitation-qPCR (ChIP-qPCR). The results indicated that ferroptosis was present in IECs from UC patients and colitis mice. Elevated expression of HIF-1α ameliorated the secretion of inflammatory cytokines and ferroptosis in IECs in vitro. HIF-1α inhibited ferroptosis by transcriptional activation of the GPX4 gene in inflammatory IECs. HIF-1α ameliorated the general conditions of mice and intestinal barrier dysfunction and by suppressing ferroptosis in IECs of mice through upregulating the expression of GPX4. In conclusion, ferroptosis occurred in the IECs of UC patients and colitis mice. HIF-1α may improve UC by suppressing ferroptosis in IECs through regulating the transcription of GPX4.